2018
DOI: 10.1038/s41551-018-0220-3
|View full text |Cite
|
Sign up to set email alerts
|

Maps of in vivo oxygen pressure with submillimetre resolution and nanomolar sensitivity enabled by Cherenkov-excited luminescence scanned imaging

Abstract: Low signal-to-noise ratios and limited imaging depths restrict the ability of optical-imaging modalities to detect and accurately quantify molecular emissions from tissue. Here, by using a scanning external X-ray beam from a clinical linear accelerator to induce Cherenkov excitation of luminescence in tissue, we demonstrate in vivo mapping of the oxygenation of tumours at depths of several millimetres, with submillimetre resolution and nanomolar sensitivity. This was achieved by scanning thin sheets of the X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 35 publications
(40 reference statements)
1
56
0
Order By: Relevance
“…One current limitation of the technique is that only two-dimensional pO 2 images can be obtained. Our previous studies have shown that threedimensional (3D) tomographic imaging of phosphorescence using light sheet excitation and diffuse optical tomography image reconstruction methods makes it possible to obtain 3D pO 2 maps with submillimeter resolution in vivo 29 . However, the tomography technique relies on thin sheet-like X-ray beams, which are not routinely used in the current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One current limitation of the technique is that only two-dimensional pO 2 images can be obtained. Our previous studies have shown that threedimensional (3D) tomographic imaging of phosphorescence using light sheet excitation and diffuse optical tomography image reconstruction methods makes it possible to obtain 3D pO 2 maps with submillimeter resolution in vivo 29 . However, the tomography technique relies on thin sheet-like X-ray beams, which are not routinely used in the current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new approach has been developed that combines phosphorescence quenching with excitation by the Cherenkov light generated within tissues that are subjected to high-energy radiation during fractionated radiotherapy [29][30][31] . This method, termed Cherenkov excited luminescence imaging (CELI), is used in the present study with the goal to directly image tumor pO 2 distributions precisely at the time of radiation delivery.…”
mentioning
confidence: 99%
“…The results of numerical simulations and in vivo experiments demonstrate that the proposed method yields accurate and robust results in terms of tumor spatial location and morphology recovery. In our future work, we would validate the SGML method in various preclinical applications and expand it to the related optical tomography including Cerenkov luminescence tomography, fluorescence molecular tomography, X‐ray luminescence computed tomography and some new imaging techniques based on Cerenkov‐excited luminescence , and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the temporal resolution of the CLI system is not optimal for clinical use. Employing an expensive advanced intensified CCD is believed helpful to refine the performance of the intraoperative CLI . A higher temporal resolution is expected to further improve the image quality and provide greater convenience for surgeons.…”
Section: Discussionmentioning
confidence: 99%